The Community Empowerment Education on Clean and Healthy Behavior (PHBS) on New Normal Adaptation in Kenagarian Singkarak, X Koto Singkarak District, Solok Regency - Nugroho Susanto; Muhammad Sazeli Rifki (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
Health is an important aspect of human life which includes physical and mental health. This is because physical and mental are two aspects that influence each other. In the midst of this COVID-19 pandemic, there are many new things that must be adapted. However, many individuals do not know how to do PHBS, which are basically all public health behaviors that are carried out on personal awareness. The things that are applied to PHBS are based on their scope, for example in the neighborhood, schools, offices, and others.The purpose of writing this article is for PHBS problems, with the Sport Healthy Management program, namely Education on Clean and Healthy Life Behavior Counseling, free examinations for the community, Interactive Dialogue on Clean and Healthy Life Behavior, Learning Practices for Clean and Healthy Life Behavior. The types of training, coaching and mentoring at the nagari that will be provided are in the form of helping to create peace and comfort in the life of a clean living community. The results of the service stated that there had been an increase in knowledge and awareness in the community regarding PHBS.